Effect of Mechanical Load Cycling on Microtensile Bond Strength of Self-Etch Systems to Dentin - Sh. Kasraei; Z. Khamverdi (Tehran University of Medical Sciences, 2008)
Objective: Optimal dentin bonding is not always obtained in clinical practice due to func-tional forces. These forces may provide stresses throughout the tooth and restorative sys-tem, which in turn may affect the adhesive bond. This experimental study evaluated the effect of load cycling on bond strength of self-etch systems. Materials and Methods: One third of the coronal portions of 48 intact human extractedupper premolars were removed. The teeth were equally divided into six groups. In groups Unloaded-Clear tri-S Bond (ULCB) and Loaded-Clear tri-S Bond (LCB), prepared dentin surfaces of each tooth were treated with Clearfil tri-S Bond (Kurary medical inc, Oka-yama, Japan), in groups Unloaded-I Bond (ULIB) and Loaded-I Bond (LIB) with I bond Heraeus Kulzer, GmbH,&Co KG, Germany), and in groups Unloaded-Xeno III (ULX) and Loaded-Xeno III (LX) with Xeno III dentin adhesives (Dentsply Detrey GmbH, Kon-stanz, Germany). Then, the teeth were restored with Filtek Supreme resin composite. After thermal cycling of the samples, Groups LCB, LIB and LX were submitted to mechanical loading (100,000 cycles, 60 N). Microtensile bond strength (MTBS) test was performed for all of groups. Two-way ANOVA and Tukey HSD tests served for statistical analysis. Results: Results showed that groups ULCB and ULIB had significantly more bond strength than group ULX (P<0.05). For all the tree adhesive systems, the MTBS values in teeth subjected to load cycling was significantly lower than unloaded teeth (P<0.001). Conclusion: Load cycling seems to decrease MTBSs of one-step adhesive systems to den-tin.